Perceived COVID-19 risk is attenuated by ingroup trust: evidence from three empirical studies - Tegan Cruwys; Mark Stevens; Jessica L. Donaldson; Diana Cárdenas; Michael J. Platow; Katherine J. Reynolds; Polly Fong (BMC, 2021)
Abstract Background The social identity model of risk taking proposes that people take more risks with ingroup members because they trust them more. While this can be beneficial in some circumstances, in the context of the COVID-19 pandemic it has the potential to undermine an effective public health response if people underestimate the risk of contagion posed by ingroup members, or overestimate the risk of vaccines or treatments developed by outgroup members. Methods Three studies (two prospective surveys, one experiment) with community-based adults tested the potential for the social identity model of risk taking to explain risk perception and risk taking in the context of COVID-19. Results Study 1 was a two-wave study with a pre-COVID baseline, and found that people who identified more strongly as a member of their neighborhood pre-COVID tended to trust their neighbors more, and perceive interacting with them during COVID-19 lockdown to be less risky. Study 2 (N = 2033) replicated these findings in a two-wave nationally representative Australian sample. Study 3 (N = 216) was a pre-registered experiment which found that people indicated greater willingness to take a vaccine, and perceived it to be less risky, when it was developed by an ingroup compared to an outgroup source. We interpret this as evidence that the tendency to trust ingroup members more could be harnessed to enhance the COVID-19 response. Conclusions Across all three studies, ingroup members were trusted more and were perceived to pose less health risk. These findings are discussed with a focus on how group processes can be more effectively incorporated into public health policy, both for the current pandemic and for future contagious disease threats.